1998
DOI: 10.2337/diabetes.47.10.1630
|View full text |Cite
|
Sign up to set email alerts
|

Plasma glucose levels are reduced in rats and mice treated with an inhibitor of glucose-6-phosphate translocase.

Abstract: The activity of glucose-6-phosphatase (G-6-Pase) in isolated rat microsomes was inhibited by a new selective inhibitor of the multi-subunit G-6-Pase system, 1-[2-(4-chloro-phenyl)-cyclopropylmethoxy]-3,4-dihydroxy-5-(3-imid azo[4,5-b]pyridin-1-yl-3-phenyl-acryloyloxy)-cyclohexanecarboxylic acid (compound A) with a 50% inhibitory concentration (IC50) of approximately 10 nmol/l. Compound A (500 nmol/l) inhibited the uptake of [14C]glucose-6-phosphate (G-6-P) into intact isolated rat microsomes, confirming that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
45
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 10 publications
5
45
0
Order By: Relevance
“…It could be objected that the down-regulation of G6pc mRNA and reduction of blood glucose level occurred too quickly, since the drug was orally administered. However, it has been reported that the blood concentration of metformin reached almost maximal level within 1 h following oral administration in the rat [34], and intraperitoneal administration of an inhibitor of G6PC translocase reduced blood glucose levels significantly 30 min after administration [35]. Furthermore, it has recently been reported that mice injected with short hairpin RNA exhibited a significant reduction in postprandial glucose levels accompanied by a decrease in G6pc expression [36].…”
Section: Discussionmentioning
confidence: 99%
“…It could be objected that the down-regulation of G6pc mRNA and reduction of blood glucose level occurred too quickly, since the drug was orally administered. However, it has been reported that the blood concentration of metformin reached almost maximal level within 1 h following oral administration in the rat [34], and intraperitoneal administration of an inhibitor of G6PC translocase reduced blood glucose levels significantly 30 min after administration [35]. Furthermore, it has recently been reported that mice injected with short hairpin RNA exhibited a significant reduction in postprandial glucose levels accompanied by a decrease in G6pc expression [36].…”
Section: Discussionmentioning
confidence: 99%
“…A major advance was derived from the cloning of murine and human glucose-6-phosphatase by Chou and co-workers [20,42] and the finding that the glucose-6-phosphatase gene is normal in patients suffering from glycogen storage disease types 1b and 1c [43]. Progress on a parallel path came with the development of a new class of highly specific high-affinity inhibitors of the glucose-6-phosphatase system that act exclusively on microsomal glucose 6-phosphate transport while leaving the enzymic phosphohydrolase activity unchanged [12][13][14][15][16][17][18]. Thus there now is convincing molecular evidence in favour of the substrate transport model of glucose-6-phosphatase.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with CGA (5-caffeyolquinic acid) (25,41,42) and its synthetic derivatives (21,43) have demonstrated their ability to inhibit hepatic G-6-Pase activity in Vitro. The synthetic derivatives also reduce the glucose release in ViVo in animal models, by both gluconeogenesis and glycogenolysis, leading to a decrease in blood glucose (21,22,42).…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence suggests that dietary polyphenols may modulate glucose absorption and metabolism (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Cohort studies have reported that high coffee consumption might be associated with a lower risk of type 2 diabetes, and this effect may be attributed to CGAs (20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation